Crimes Against Women: From Violence to Homicide - Abrunhosa, Catarina (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) is a highly prevalent phenomenon worldwide and is considered a severe violation of human rights. Intimate partner homicide (IPH) and attempted intimate partner homicide (AIPH) although less frequent have a severe direct or indirect impact on victims. Despite the vast literature on IPV and IPH, there is still scarce research on AIPH. Thus, this study aimed to analyze whether perpetrators of IPV, IPH, and AIPH differ from each other, as well as to identify the factors that predict violence in intimacy. For those purposes, we performed a comparative analysis between 50 male individuals convicted of IPH, 27 convicted of AIPH, and 168 convicted of IPV from Portugal. The data were collected using an interview and a set of psychological measures. Results revealed that, although IPV, IPH, and AIPH perpetrators’ share some characteristics, significant differences were found between them. IPV perpetrators were more prone to perpetrate violent behaviors against an intimate partner or ex-partner than IPH or AIPH offenders. The use of weapons and separation from the victim increases the probability of committing IPH or AIPH. Being divorced, having no children, and committing other crimes than domestic violence are predictors of AIPH. These results have some practical implications, in terms of both risk prediction and risk management. Accurate and comprehensive tools should be included as a routine in the primary care services, as well as in the child care services and in victim support services. Prevention and intervention efforts must be comprehensive, involving work with perpetrators and victims.